Correlación de determinaciones bioquímicas al usar dos tipos diferentes de tubos para muestras sanguíneas - Suárez S., Claudio; Araneda F., María Nelly; Tong S., Ana María; Vial C. , María Jesús; Aldunate O., Jorge (Revista Hospital Clínico Universidad de Chile, 2007)
The impressive development of the clinical laboratory network of the HCUCH has forced a complete protocol revision, specially directed towards the procedures involved in way the biological samples are obtained. This includes the selection of the tubes used. In this sense, the use in the different centers of SS tubes, which stands for serum separating tubes, was evaluated. The SS tubes consist of a gel that which after centrifugation separates the thrombotic and serum phases, forming an impermeable barrier in between. Before its onset, is necessary to compare with the aid of the bio-statistical parameter of correlation coefficient both the biochemical and hormonal measurements obtained through the use of the typical tubes (containing heparin or without anticoagulant reactive) and those of the SS tubes. The determinations included 27 parameters, consistent of biochemical, electrolytic and hormonal measurements. The data collected was tabulated and afterwards the statistical analysis was performed, considering correlation and concordance, and then the interclass Correlation coefficient (ICC) was applied. The concordance study concluded that 26 of the 27 evaluated parameters have a value of ICC between 0.858 and 1.0, Only the direct bilirrubin showed a low ICC (0.08), possibly, it must be considered the low values of it found in the samples, and therefore to make the result to significant the evaluation has to be made among a greater number of samples. In summary, the results supported the adoption of tubes SS for the clinical laboratories processes, since these threw equivalent and trustworthy results compared with the conventional tubes for the medical studied with advantages in operator protection and samples transport.